Enhancing High School Physics Learning Through Augmented Reality: A Bibliometric and Systematic Review - Tugirin, Tugirin; Kuswanto, Heru; Ramazhoni, Deo Alfitra; Putri, Rahmania Amanah; Muslim, Riyadi; Moore, Jordan Kyle (Jurnal Pendidikan Progresif, 2025)
Enhancing High School Physics Learning Through Augmented Reality: A Bibliometric and Systematic Review. Objective: This study aims to investigate the research trends, opportunities, effectiveness, and challenges of implementing Augmented Reality (AR) technology in physics education through a systematic literature analysis. Methods: This research employed a bibliometric and systematic review approach of 45 selected journal articles obtained from the Scopus database. Data were extracted on May 2, 2025, covering publications from 2020 to 2025. The initial search using the keywords "(augmented reality) AND (physics learning)" yielded 167 documents, which were rigorously filtered based on inclusion and exclusion criteria. The analysis was conducted using the Biblioshiny (R) software to generate thematic maps, publication trends, and collaboration networks. Findings: The findings reveal that AR technology provides significant opportunities to develop interactive, immersive, and contextual physics learning experiences, particularly in visualizing abstract physics concepts. AR has proven effective in enhancing students’ conceptual understanding, scientific literacy, and critical thinking skills. However, its implementation still faces crucial challenges, including a lack of curriculum-aligned content, limited technical infrastructure, and insufficient teacher training. Conclusion: Integrating AR technology into the physics curriculum has demonstrated a significant and positive impact on enhancing learning quality. Successful implementation depends on collaborative efforts among curriculum developers, educators, and policymakers to overcome the identified challenges. These findings provide a strategic foundation for developing sustainable, adaptive, and relevant physics education in the digital era. Keywords: augmented reality, conceptual understanding, physics learning, biblioshiny, systematic literature.